A Progressive View on Religion and Modern Art - Fowler, Cynthia (Religion and the arts, 2015)
This article examines the Religious Art of Today exhibition, originally held in 1944 at Boston’s Institute of Modern Art and then reformulated for the Dayton Art Institute in Ohio. The exhibition was eclectic in that it included a wide range of artists and a diversity of faiths, and engaged the debate held among museum professionals about the relationship between religion and modern art. The article focuses closely on Catholic, Jewish, and Navajo art included in the exhibition. The IMA’s commitment to the figurative tradition afforded artists the opportunity to explore their identities—as Jews, as Catholics, as Navajos—using recognizable religious subjects. That the works in the exhibition were selected as representative of modern art resulted in a convergence of discourses related to modern art with those of religious/cultural identity.